FORMULATION AND EVALUATION OF HERBAL OIL-BASED ITRACONAZOLE CREAM FOR FUNGAL INFECTION - KUMAR, INDER; THAKUR, BHUMIKA; SHARMA, ANKITA; THAKUR, REENA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The current study was to formulate and to evaluate itraconazole herbal oil-based cream for fungal infection. Methods: Six herbal oils were used for the formulation of itraconazole creams, namely, mustard oil (MO), olive oil (OO), wheat germ oil (WGO), jojoba oil (JO), tea tree oil (TTO), and combined oil (CO). Creams were formulated by the trituration method. Each herbal oils containing three different formulations of different concentrations of oils. Results: All the prepared formulation was evaluated successfully. Out of all the formulations from each herbal oils the best two formulations were finalized, that is, MO2 and CO2 which show the greater in vitro diffusion rate among all. Formulation MO2 shows 55.45±0.10% and CO2 showed 59.43±1.18% within 480 min, respectively. Optimized formulations were also compared with the marketed formulation, which results in formulation CO2 as the best formulation among all. Conclusion: It can be concluded that herbal oil-based cream proved better alternate than oral preparation and improve patient compliance, ease of administration, local bioavailability, and better proves for fungal infected patients.